2021
DOI: 10.32942/osf.io/3tdfk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcription factors evolve faster than their structural gene targets in the flavonoid pigment pathway

Abstract: Evolutionary transitions in flower color often trace back to changes in the flavonoid biosynthetic pathway and its regulators. In angiosperms, this pathway produces a range of red, purple, and blue anthocyanin pigments. Transcription factor (TF) complexes involving members of the MYB, bHLH, and WD40 protein families control the expression of pathway enzymes. Here, we investigate flavonoid pathway evolution in the Petunieae clade of the tomato family (Solanaceae). Using transcriptomic data from 69 species of Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…While we cannot rule out the possibility that structural genes can also accumulate mutations prior to the reduction in transcription, this observation is in line with a previous study that observed faster evolutionary changes in transcription factors than in structural genes [95]. Similarly, Wheeler et al [93] showed that transcription factors, particularly MYB, presented lower levels of gene expression with higher molecular evolutionary rate compared to their targeted structural genes, and suggested a negative correlation between evolution rate and gene expression in the Petunieae tribe [93]. This premise commonly known as the E-R anticorrelation, has been widly studied across different organisms, including yeast [104,105], Arabidopsis [106], Brassica [107], Barley [108], Arachis [109],…”
Section: Transcription Factor Variations Appear Frequently As Block T...supporting
confidence: 91%
See 4 more Smart Citations
“…While we cannot rule out the possibility that structural genes can also accumulate mutations prior to the reduction in transcription, this observation is in line with a previous study that observed faster evolutionary changes in transcription factors than in structural genes [95]. Similarly, Wheeler et al [93] showed that transcription factors, particularly MYB, presented lower levels of gene expression with higher molecular evolutionary rate compared to their targeted structural genes, and suggested a negative correlation between evolution rate and gene expression in the Petunieae tribe [93]. This premise commonly known as the E-R anticorrelation, has been widly studied across different organisms, including yeast [104,105], Arabidopsis [106], Brassica [107], Barley [108], Arachis [109],…”
Section: Transcription Factor Variations Appear Frequently As Block T...supporting
confidence: 91%
“…A study published by Rausher et al [92] proposed that the evolutionary rate of enzymes depends on their location in a pathway with early genes showing a slower mutation rate, but this has been contradicted recently [93]. According to the Arabidopsis Information Resource (TAIR), the length of the coding sequence (CDS) of DFR is 1149 bp (accession: NM_123645) and of ANS is 1071 bp (accession: NM_118417).…”
Section: Dfr Is the Block Hotspot In The Anthocyanin Branchmentioning
confidence: 99%
See 3 more Smart Citations